IL‐23‐ and Imiquimod‐Induced Models of Experimental Psoriasis in Mice. (7th January 2019) - Singh, Tej Pratap; Zhang, Howard H.; Hwang, Samuel T.; Farber, Joshua M.
Abstract: Genome‐wide association studies have found that polymorphisms in genes for IL‐23 and its receptor are important in psoriasis, and blocking IL‐23 is an effective therapy in the disease. The use of Aldara ™, a cream that contains the TLR7 and TLR8 agonist imiquimod (IMQ), was found to exacerbate psoriasis in some patients with pre‐existing disease. Intradermal injections of IL‐23 and topical application of Aldara/IMQ induce skin inflammation in mice with features similar to psoriasis—including epidermal hyperplasia and accumulation of inflammatory cells in epidermis and dermis—which is mediated by IL‐17A, IL‐22, and other factors implicated in the human disease. Consequently, these models can be used in preclinical studies to investigate the molecular and cellular pathogenesis of psoriasis, as well as in the evaluation of potential therapies. This article provides detailed methodologies for creating and evaluating the IL‐23‐ and Aldara/IMQ‐induced mouse models of psoriasis. The article also provides a protocol for analyzing skin leukocytes by flow cytometry. © 2019 by John Wiley & Sons, Inc.